Integrasi Nilai-Nilai Islam Dalam Pembelajaran Ilmu Pengetahuan Sosial di SMP Al-Hidayah Medan - Dika Darmina; Masganti Sitorus; Ripho Delzy Perkasa (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2023)
The objectives of this study were: (1) to find out social studies learning plans that are integrated with Islamic values, (2) to find out the teacher's strategy in the teaching and learning process of social studies learning that is integrated with Islamic values, (3) to find out the supporng factors and obstacles to the integration of Islamic values in social studies learning at SMP Al-Hidayah Medan. This study uses a qualitative approach, with a phenomenological approach. Collecting research data using interview techniques, observation and documentation. Informants in this study included school principals, student affairs, social studies subject teachers and students of SMP Al-Hidayah Medan. After the data is processed then it is analyzed by data reductiondata presentation, data verification and drawing conclusions. Based on the results of the study, it can be concluded that: (1) the social studies learning plan used by SMP Al-Hidayah Medan teachers is in the form of lesson plans that have been integrated with Islamic values, and supported by superior programs in schools with Islamic nuances (2) The strategy used teachers of SMP Al-Hidayah Medan in integrating Islamic values into social studies subjects using problem-based learning strategies or problem-based learning which is a strategy model that can foster student creativity in solving social problems (3) there are several supporting factors in the application of the integration of Islamic values in social studies learning, namely: situations and conditions of the learning environment that are characteristic of Islam, adequate facilities and teacher understanding in the field of religion. As well as there are also factors inhibiting the integration of Islamic values in social studies learning, namely: differences in student characteristics and the feeling of boredom or boredom experienced by students due to dense learning.n service to the public and website visitors related to the North Sumatra Education Office. Keywords: Integration, Islamic Values, Social Studies